Teacher's Competence: Applying the Problem-Based Learning Model through Academic Supervision - Juni Agus Simaremare; Nancy Angelia Purba (International Journal of Asian Education, 2021)
This study aimed to improve the professional competence of Indonesian language teachers in applying the Problem-Based Learning (PBL) learning model at State Senior High School 1 Muara. This research is a Classroom Action Research involving 6 Indonesian language teachers. The research was conducted in two cycles, namely: planning, implementation, observation, and reflection. Aspects measured in the observations were teacher teaching performance, teacher interaction with researchers, interaction with other Indonesian language subject teachers, collaboration with other teachers, making lesson plans, learning processes, evaluating the implementation of Problem-Based Learning (PBL). From the data analysis, it was found that there was an increase in teacher activity and competence in implementing the PBL model. In the initial condition, from 54.00 (criteria for poor score) increased to 66.00 (criteria for sufficient value) and 76.00 (criteria for good value). In the aspect of learning implementation, the average score of 55.21 (criteria for low scores) increased to 65.43 (sufficient value criteria) and 75.43 (good value criteria) in the second cycle. In the aspect of assessment of learning outcomes, from an average of 53.58 (criteria for poor scores) to 65.42 (criteria for good scores) and 77.42 (criteria for good scores). Also, in the aspect of classroom management from 54.00 enough and 75.83 ( good grade criteria). From the results above, it can be concluded that the implementation of the Problem-Based Learning model with academic supervision has been proven to improve the professional competence of teachers in managing the learning process